Early miscarriage rate in lean polycystic ovary syndrome women after euploid embryo transfer – a matched-pair study. Issue 5 (November 2017) - Luo, Lu; Gu, Fang; Jie, Huying; Ding, Chenhui; Zhao, Qiang; Wang, Qiong; Zhou, Canquan
Abstract: The early miscarriage rate is reported to be higher in patients with polycystic ovary syndrome (PCOS) compared with non-PCOS patients. However, whether PCOS is an independent risk factor for early miscarriage is still controversial; to what extent embryonic aneuploidy accounts for miscarriages of PCOS is still unknown. In this 1:3 matched-pair study, 67 lean PCOS patients and 201 controls matched for age, body mass index (BMI) and embryo scores undergoing a single euploid blastocyst transfer in vitrified-warmed cycles were analysed. Clinical pregnancy, early miscarriage and live birth rates were compared. Logistic regression analysis was performed to further evaluate the factors associated with early miscarriage and live birth. Clinical pregnancy rates were 50.7% in PCOS and 55.2% in control groups. Early miscarriage rate was significantly ( P = 0.029) increased in the PCOS group compared with controls; non-PCOS patients had a significantly higher live birth rate than PCOS patients, P < 0.001. Further regression analyses showed that PCOS was significantly associated with a higher risk of early miscarriage and decreased chance of live birth. In conclusion, PCOS in women undergoing pre-implantation genetic diagnosis may, independently from BMI and karyotype, increase the risk of miscarriage.